VALUE CO-CREATION IN SMEs: A FIFTEEN-YEAR BIBLIOMETRIC ANALYSIS OF EMERGING TRENDS AND RESEARCH DIRECTIONS - Ni Made Purnami; Ni Wayan Mujiati; Ayu Putu Laksmi Danyathi; Desak Komang Dea Marcellina Putri Darmadi; Uswatun Siwi Kartika Sari (Jurnal Manajemen Sains dan Organisasi, 2024)
Objective – This study aims to conduct a bibliometric analysis of the evolution and emerging trends in value co-creation within Small and Medium Enterprises (SMEs) over the past fifteen years. Design/Methodology/Approach – A total of 529 research and review articles from the ScienceDirect database were analyzed using VOSviewer software to identify key clusters and trends in value co-creation research. Findings – The analysis identified seven significant clusters in the literature: Digital Marketing and Customer Engagement, Service Innovation and Service-Dominant Logic, Customer Experience and Loyalty, Social Capital and Stakeholder Engagement, Technology-Enabled Value Co-creation, Sustainable and Ethical Value Co-creation, and Co-creation in Emerging Markets. These clusters highlight the growing importance of integrating advanced technologies, sustainability practices, and tailored strategies for different market contexts in value co-creation. Conclusion and Implications – The findings provide actionable insights for SMEs to implement effective value co-creation strategies, emphasizing the importance of adapting to technological advancements and sustainability trends. The study also identifies research gaps, suggesting areas for future research, including the role of artificial intelligence in value co-creation and the impact of sustainable practices on SME performance.